The Good Faith Principle and the Transformation of Contract Law in a Globalized Legal Order - Dahris Siregar (jfpublisher, 2026)
By examining the viewpoint of international law and comparing the global legal system. This study attempts to assess how the concept of good faith has changed in the context of contract law in the age of globalization. The issue raised by Article 1338 of the Civil Code, which describes Indonesia's good faith notion, serves as the study's backdrop, is still declarative and lacks adequate operational power. This situation diminishes the parties' protection and results in inconsistent application of contract law. This research is urgent because more cross-border transactions and digital contracts are required, which calls for global criteria of integrity and fairness. The method is normative juridical research with a descriptive-analytical approach, utilizing secondary legal materials from relevant scientific literature in addition to primary legal resources in the form of national and international legal instruments. The effort to create a concept of good faith principle change that is realistic and in line with global practice, in order to incorporate it into Indonesian law without ignoring the characteristics of civil law, is what distinguishes this research from others. The study's findings demonstrate how, globally, the application of the good faith notion has changed from moral to legally required standards. Indonesia must follow suit by establishing specific normative standards in order to make its national contract law more adaptable to the forces of globalization and technological advancements.